Ochrona interesu rodziny a zmiana generacji w rolnictwie - Zieliński, Andrzej (Wydział Prawa i Administracji UAM, 1985)
The contemporary Polish village requires and expects a modernisation in practically all areas of its activities and activeness. It is the young generation that is to play the greatest part in the process of structural changes in the Polish country. A rejuvenation of farming is not only desirable, but necessary, and it should be consciously stimulated. Yet a doubt appears if the generation change in farming is not taking place at the cost of an infringement of the interests of the nearest family. The problem is analised on the basis of the Social Security of Individual Farmers Act of 14 December, 1982, (Government Regulations and Laws Gazette 40, pos. 268), and the Civil Code provisions for the inheriting of farms. Furthermore, it seems that the problem is topical only in those families in which there appear conflicts; in families of close bonds the legal regulation of certain social relations is not an obstacle to patterns of behaviour preserved in village tradition. As far as the retirement pension act is concernred members of the transferring farmer's family are not entitled to any claims against the one who transfers as well as against the recipient. The Act determines only what the duties of the recipient towards the one who transfers are, the range of which are, besides, very limited; their bulk is taken over by the state. The Act further, does not mention any possible settlement of accounts between the recipient of the farm and the family of the transferring farmer, in the event of the latter's death. There is an evident gap in the act in this respect. De lege lata there exists only the slightest hope that in the event of such a death, an inheritance would be left in which the farmer's successor would participate. A number of changes have been introduced with respect to succession to farms in the course of the last two decades, which testify to a certain openness, on the legislator's part, to reality, although in all that time he or she has remained faithful to the conception that the successor to a farm must comply with additional prerequisites. What deserves special notice is, first of all, the widened range of those entitled to statutory succession and, secondly the possibility of succeeding to a farm on general terms. On the other hand, one can observe that present regulations pay only a very scant attention to the contribution the testator's family make to the creation of the inherited objects by decidedly favouring socio-economic reasons. It seems that practice should follow a more liberal interpretation of the provisions for the succession to farms. A guideline might be sought in the instructions to the administration of justice and to judicial practice expressed in a Supreme Court resolution of 1968. In cases of a statutory succession to farms, a somewhat singular issue appears in the form of succession by so-called specific replacement. In view of the fact that in a given situation the more far-off members of the testator's family might participate in the succession, for e. g. the descendants of brothers and sisters, this type of succession is an occasion when tension in the family might appear, although also in this case the gist of the problem lies in the conditions to be met by the successor to the farm. In cases of testamentary succession the very principle of freedom of bequest is a potential source of misunderstandings and might lead to those members of the family not appointed as heirs being injured. But also in such cases, the successor must possess specific attributes entitling him to the appointment. Should those be lacking, it might turn out that statutory succession would take place, which would alleviate somewhat the distress connected with bequething. What turns out to be rather ineffective in testamentary succession to farms is the institution of legitimate portions, as here also those who might wish to gain from it, have to conform to certain prerequisites as potential heirs. Quite serious irregularities might be observed in distributive proceedings. They resolve themselves into an assessment of the inherited farm's capacity of payment by installments, to the lowering of payments. The legislator appears here as the protector of the farmer obliged to payments, whereas the farmer and both the testator's and the obliged farmer's family are all entitled.
The Protection of the Family Interest and the Generation. Change in Farming